96-Week Resistance Analyses of Rilpivirine in Treatment-Naive, HIV-1-Infected Adults from the Echo and Thrive Phase Iii Trials. Issue 8 (November 2013) - Rimsky, Laurence; Van Eygen, Veerle; Hoogstoel, Annemie; Stevens, Marita; Boven, Katia; Picchio, Gaston; Vingerhoets, Johan
Background: In the ECHO/THRIVE 96-week efficacy analysis, the response rate was 78% with rilpivirine (RPV) and efavirenz (EFV) plus two nucleoside/nucleotide reverse transcriptase inhibitors. Methods: For resistance analyses, virological failures (VFs) were genotyped and/or phenotyped at baseline and failure. Results: In the overall 96-week resistance analyses, the proportion of VFs was higher with RPV (96/686, 14%) versus EFV (52/682, 8%), but similar within weeks 48–96 (22/686, 3% versus 16/682, 2%). In genotyped VFs, treatment-emergent non-nucleoside reverse transcriptase inhibitor (NNRTI) resistance-associated mutations (RAMs) were as common with RPV (46/86, 53%) versus EFV (20/42, 48%), but nucleoside/nucleotide reverse transcriptase inhibitor RAMs were more common with RPV (48/86, 56%) than EFV (11/42, 26%). In RPV VFs, E138K+M184I remained the most frequent combination. Among RPV VFs with phenotypic RPV resistance, cross-resistance was observed with nevirapine (16/35, 46%), EFV (30/35, 86%) and etravirine (32/35, 91%). Among patients with baseline viral load (VL)≤100, 000 copies/ml, there were fewer VFs (RPV: 28/368, 8%; EFV: 20/329, 6%), fewer VFs with treatment-emergent NNRTI RAMs (RPV: 10/27, 37%; EFV: 6/17, 35%), and less phenotypic resistance to RPV and other NNRTIs, than in patients with baseline VL>100, 000 copies/ml (VFs: 68/318, 21% [RPV], 32/353, 9% [EFV]; NNRTI RAMs: 36/59, 61% [RPV], 14/32, 56% [EFV]). Among RPV VFs with baseline VL≤100, 000 copies/ml observed within weeks 48–96, only 1/7 had phenotypic resistance to RPV. Conclusions: During the second year of treatment in ECHO/THRIVE, few VFs with emerging NNRTI RAMs (no new RPV RAMs) occurred.